Cooperative-Based Economic Empowerment: The Role of the Merah Putih Cooperative in Promoting Community Self-Reliance - Pinky Nadila; Hendra Riofita (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
Community economic independence is a pillar of national welfare, but is often hampered by dependence on third-party capital and limited financial management. This study aims to analyze the strategic role of the Merah Putih Cooperative in encouraging members' economic independence through inclusive capital access and business development. The method used is qualitative with a Systematic Literature Review (SLR) approach and narrative review. Data were collected through the Google Scholar database with the inclusion criteria of articles published in the last ten years (2016–2026). A total of 10 selected articles were analyzed using thematic analysis techniques to map cooperative strengthening strategies. The results show that cooperative economic independence rests on three main foundations: (1) Transparent and professional organizational governance, which has been proven to increase member loyalty by up to 30% and operational efficiency; (2) Strengthening human resource capacity and digital transformation, where the adoption of e-commerce and fintech technology can expand market access and increase the average income of members; and (3) Internalization of the value of cooperation reinforced by government regulatory support. A literature synthesis concludes that the integration of modern management and a spirit of collectivism makes the Merah Putih Cooperative an effective instrument for reducing economic disparities and strengthening people's economic sovereignty in the modern era.